2017
DOI: 10.1186/s40101-017-0137-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quantity and intensity of pulsed light on human non-visual physiological responses

Abstract: BackgroundExposure to pulsed light results in non-visual physiological responses in humans. The present study aims to investigate whether such non-visual effects are influenced to a greater extent by the intensity of lighting or by the power (quantity) of lighting.Methods>Twelve healthy young male participants (23 ± 0.3 years, 21–24 age range) were recruited for the present study. Participants were exposed to light of varying levels of intensity and quantity whose frequency was held constant across the conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The development of artificial lighting systems has allowed us to have a bright environment at night, bringing comfort and safety. However, light has also been reported to have a range of physiological impacts on humans, such as changes in pupillary constriction [ 1 4 ], autonomic nervous function [ 5 7 ], brain activity [ 8 ], and cortisol secretion [ 9 ]. Furthermore, bright light at night is known to delay the circadian phase [ 10 12 ], resulting in disruption of the circadian rhythm [ 13 ], which, in turn, can lead to poor sleep and various kinds of health risks, such as cardiac disease and depression [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of artificial lighting systems has allowed us to have a bright environment at night, bringing comfort and safety. However, light has also been reported to have a range of physiological impacts on humans, such as changes in pupillary constriction [ 1 4 ], autonomic nervous function [ 5 7 ], brain activity [ 8 ], and cortisol secretion [ 9 ]. Furthermore, bright light at night is known to delay the circadian phase [ 10 12 ], resulting in disruption of the circadian rhythm [ 13 ], which, in turn, can lead to poor sleep and various kinds of health risks, such as cardiac disease and depression [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, we found that the pupillary response under the extremely short (pulse width 100 μs) but higher irradiance (11.2 μW/cm 2 or 13.4 log photons/cm 2 /s) blue-pulsed light was significantly greater than that under the steady blue light (1.4 μW/cm 2 or 12.5 log photons/cm 2 /s) which had equal blue light components (the products of irradiance and duration) [ 12 ]. We assumed that the pulsed light of strong irradiance might induce significantly greater pupillary response [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…[64]2016Blue (10, 5, 2 lx)Green (71 lx)Red (39 lx)(OLED)Time zone of experiment: 08:30–13:00·Heart rate·HRVYuda E, Ogasawara H, Yoshida Y, Hayano J. [65]2017Blue (483 nm, 13 lx)Green (555 nm, 91 lx)White (158 lx)(OLED)Exposure time: 10 min + 5 min PVT under white fluorescent light (illuminance, 300 lx)Psychomotor vigilance test (PVT)Time zone of experiment: 09:30–14:00·Heart rate·HRV·Reaction time, minor lapse (PVT)Dai Q, Uchiyama Y, Lee S, Shimomura Y, Katsuura T. [61]2017Blue (467 nm)Irradiance: 7.5, 15, 30 μW/cm 2 Pulse width: 50, 100, 200 μsWhite (color temperature 2878 K, 14.75 μW/cm 2 ) (LED)Exposure time: 12 min·Pupillary constriction·EEG·Subjective evaluation (concentration, sleepiness, perception of blueness)Yuda E, Ogasawara H, Yoshida Y, Hayano J. [66]2017Blue (485 nm, 8.02 μW/cm 2 )Orange (622 nm, 6.54 μW/cm 2 )(OLED)Exposure time: 30 min during lunch break5 min of PVT under white fluorescent light (color temperature 4010 K, illuminance 450 lx)Psychomotor vigilance test (PVT)·Heart rate·HRV·Reaction time, minor lapse (PVT)Lee S, Muto N, Shimomura Y, Katsuura T. [62]2017Blue (466 nm)Green (527 nm)Irradiance: 20 μW/cm 2 Pulse width: 1 msInter-stimulus interval: 0, 250, 500, 750, 1000 ms·Pupillary constrictionLee S, Uchiyama Y, Shimomura Y, Katsuura T. [63]2017Blue (464 nm)Green (526 nm)Pulse width: 2.5 msPhoton density: 15.2 log photons/cm 2 /sBlue, green, blue + green·Electroretinogram (ERG)·EEG·Visual evoked potential·Pupillary constriction·Subjective evaluations (bluish, greenish)Kozaki T, Hidaka Y, Takakura JY, Kusano Y.…”
Section: Nonvisual Effects Of Monochromatic Lightmentioning
confidence: 99%
“…Pupillary constriction was found to be greater under high irradiance with short pulse width and under middle irradiance with middle pulse width, when compared with low irradiance with long pulse width condition. These findings indicate that higher intensity with shorter pulsed width of blue pulsed light produces a more significant influence on ipRGCs, even when the quantity of blue pulsed light is held constant [61]. The effects of both simultaneous and successive exposure to blue and/or green pulsed light on PLR were investigated using extremely short pulses (1 ms) of blue and green lights with inter-stimulus intervals (ISIs) ranging from 0 to 1000 ms.…”
Section: Nonvisual Effects Of Monochromatic Lightmentioning
confidence: 99%